PERAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR DALAM MEMEDIASI HUBUNGAN MOTIVASI KERJA, BUDAYA ORGANISASI, DAN KINERJA PADA PEGAWAI DINAS PENDIDIKAN DAN KEBUDAYAAN KOTA PADANG - Candra Yolanda; Elfiswandi; Jhon Veri (Journal Publicuho, 2025)
This study aims to examine the effect of work motivation and organisational culture on performance mediated by organisational citizenship behaviour. A quantitative approach with hypothesis testing techniques was used in this study. There were 94 samples with the saturated sample technique, namely all employees at the Padang City Education and Culture Office, West Sumatra Province. Data were collected through distributing questionnaires online and processed using SmartPLS 3.0 software with structural equation modelling techniques. The results indicated that work motivation and organisational culture each had a positive and significant effect on organisational citizenship behaviour. Work motivation and organisational citizenship behaviour each have a positive and significant effect on performance, but are not significantly affected by organisational culture. Organisational citizenship behaviour can mediate the relationship between work motivation with performance, and organisational culture with performance. The research implications emphasise the importance of increasing the sense of belonging, strong bonding, and high dedication in the agency environment in order to produce employee loyalty and good work quality.